Proximity to a hazardous waste thermal treatment facility alters human physiology: a community-driven pilot study - Avinash Kumar; Avinash Kumar; Chuqi Guo; Qudus Sarumi; Christopher Courtney; Shawn Campagna; Shawn Campagna; Jennifer Richmond-Bryant; Stephania A. Cormier; Stephania A. Cormier (Experimental Biology and Medicine)
Open burn/open detonation (OB/OD) disposes of explosive waste via uncontrolled combustion, releasing harmful pollutants like toxic gases and particulate matter. Colfax, Louisiana, houses the nation’s only commercially OB/OD thermal treatment (TT) facility, raising concerns about environmental and public health impacts due to its emissions. In this exploratory pilot study, we investigated metabolic alterations indicative of potential health impacts from exposure to emissions from a TT facility through an untargeted metabolomics analysis of urine samples obtained from local residents. Urine samples were collected from 51 residents living within a 30-km radius of the facility, with proximity, race, and sex as key variables. Samples were analyzed using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS) to identify metabolic alterations and potential biomarkers of exposure. A total of 217 metabolites were identified, with significant differences in abundance based on proximity to the facility. Key metabolic pathways affected included energy metabolism, amino acid metabolism, and oxidative stress-related pathways. Metabolites associated with oxidative stress, such as glutathione sulfonamide (GSA), were elevated in individuals residing closer to the facility, indicating increased oxidative stress. Alterations in the glutathione/glutathione disulfide (GSH/GSSG) ratio further highlighted redox imbalances. Pathway enrichment analyses revealed perturbations in glycolysis, citric acid cycle, sulfur metabolism, and nucleotide metabolism, which are linked to critical biological functions like energy production and DNA repair. Notable differences in metabolite profiles were also observed between sexes and racial groups, pointing to the interplay of intrinsic biological and environmental factors. These findings demonstrate that exposure to emissions from the TT facility may have significant impacts on human health, including disruptions in cellular metabolism and increased oxidative stress. Further research is crucial to understand the long-term health implications of these metabolic alterations and to develop strategies to mitigate the environmental and health risks associated with this facility.